Coping strategies as mediating mechanisms between adolescent polysubstance use classes and adult alcohol and substance use disorders. (April 2023) - Elam, Kit K.; Mun, Chung Jung; Connell, Arin; Ha, Thao
Highlights: We identified 3 classes of polysubstance use in adolescence: high, experimental, and low. Youth in the high and experimental classes had greater aggressive, reactive, and substance use coping strategies across adolescence and young adulthood. Aggressive, reactive, and substance use coping strategies were differentially associated with substance use disorder and alcohol use disorder in adulthood. Collectively, adolescent polysubstance use contributes to maladaptive coping strategies which increase risk for alcohol use disorder and substance use disorder in adulthood. Abstract: Adolescent polysubstance use is a robust predictor of substance use in adulthood and can be exacerbated by poor coping with stress over time. We examined whether latent classes of adolescents' polysubstance use predicted alcohol use disorder and substance use disorder diagnoses in adulthood via multiple stress coping strategies. Self-reported frequency of past 3-month alcohol, tobacco, and marijuana use in 792 adolescents (aged 16/17) were used to form latent classes of polysubstance use. Self-reported aggressive, reactive, substance use and cognitive coping strategies (ages 18/19, 22/23, 23/24) were examined as multiple mediators of polysubstance use classes and alcohol use disorder and substance use disorder in adulthood (age 26/27) controlling for demographic covariates. Latent class analysis resulted in High, Experimental, and Low polysubstance use classes. Those in high and experimental polysubstance use classes, compared to those in the low polysubstance use class, had greater use of aggressive and reactive coping strategies, which respectively predicted greater substance use disorder and alcohol use disorder in adulthood. Across all comparisons (high vs low, experimental vs low, and high vs experimental), higher polysubstance use was associated with greater substance use coping, which predicted both alcohol and substance use disorder. Greater polysubstance use, even experimental use, in adolescence is a significant risk factor for developing alcohol use disorder and substance use disorder in adulthood and this occurs, in part, via maladaptive stress coping strategies.